Penggunaan Social media influencer Sebagai Usaha Membangun Budaya Masyarakat Digital Tentang Konsep Tubuh Ideal dan Kepercayaan Diri - Azizun Kurnia Illahi; Dewanto Putra Fajar; Muhammad Irawan Saputra (Jurnal Komunikasi, 2020)
Social media influencers have a wide influence on users of social media, by entering new messages or popularizing certain issues. This makes the audience more aware of a particular issue in society, including on the topic of self-confidence or about the ideal body shape for women. The discussion about self-confidence or ideal body shape becomes a serious and important discourse for modern society. So that the activity of spreading information about it becomes important for the audience, because of that the role of influencer social media is important to know, especially on messages presented in social media. This research uses qualitative methods, with qualitative content analysis methodology. The purpose of this study is to determine the role of influencers in social media in providing messages relating to the ideal body concept to build self-confidence. The use of content analysis makes the writer have a better chance to provide deeper observation and analysis of the textual aspects of messages in social media, especially messages related to self-confidence and ideal body shape. This article finally gets important empirical findings that social media influencers have a big role to play in important information for social media users, which traditional media cannot tend to provide. Content created by social media influencers as communicators provides a new understanding of ideal body concepts that are not only related to physical appearance and beauty but also relate to the way individuals maintain body health. Social media influencer memberikan pengaruh luas kepada pengguna media sosial, dengan cara memasukkan sejumlah pesan baru atau mempopulerkan isu tertentu. Hal itu menjadikan audiens menjadi lebih sadar tentang suatu isu tertentu dalam masyarakat, termasuk juga pada topik tentang kepercayaan diri atau tentang bentuk tubuh ideal bagi perempuan. Adanya bahasan mengenai kepercayaan diri atau pun bentuk tubuh ideal menjadi wacana serius dan penting bagi masyarakat modern. Sehingga aktivitas penyebaran informasi tentang hal itu menjadi penting bagi audiens, karena itu peran sosial media influencer menjadi penting untuk diketahui, khususnya pada pesan-pesan yang disajikan di dalam media sosial. Penelitian ini menggunakan metode kualitatif, dengan metodologi analisis isi kualitatif. Tujuan penelitian ini adalah mengetahui peran social media influencer dalam memberikan pesan berkaitan dengan konsep tubuh ideal untuk membangun kepercayaan diri. Penggunaan analisis isi menjadikan penulis memiliki kesempatan lebih baik untuk memberikan pengamatan dan analisis lebih dalam terhadap aspek teksktual pesan dalam media sosial, khususnya pesan-pesan terkait dengan kepercayaan diri dan bentuk tubuh ideal. Artikel ini pada akhirnya mendapatkan temuan empiris penting bahwa social media influencer memiliki peranan besar untuk memasukkan sejumlah informasi penting bagi pengguna media sosial, yang cenderung tidak bisa diberikan oleh media-media tradisional. Konten-konten yang dibuat oleh social media influencer sebagai komunikator memberikan pemahaman baru tentang konsep tubuh ideal yang tidak hanya berkaitan dengan penampilan fisik dan kecantikan tetapi juga berhubungan dengan cara individu menjaga kesehatan tubuh.